Emphysematous cystitis with rare findings of subcutaneous emphysema and extraperitoneal pelvic gas: a case report - Gunawardene, Milan C.; Ambegoda, Madura C.; Willaraarachchi, Munipriya A.; Abeygunasekera, Anuruddha M. (International Surgery Journal, 2021)
Emphysematous cystitis is a rare form of lower urinary tract infection with pathognomonic intramural and intraluminal gas. It commonly occurs in elderly females with uncontrolled diabetes mellitus. Subcutaneous emphysema and extraperitoneal pelvic gas are reported as rare presentations of emphysematous cystitis. Here we report emphysematous cystitis occurring in an elderly male with multiple co-morbidities who presented with fulminant sepsis and rare findings of subcutaneous emphysema and extraperitoneal pelvic gas.